Impact of Coastal Flood on Building, Infrastructure, and Community Adaptation in Bukit Bestari Tanjungpinang - Hanif, Muhammad; Putra, Beben Graha; Hidayat, Rizki Atthori; Ramadhan, Ravidho; Ahyuni, Ahyuni; Afriyadi, Afriyadi; Wan Moh Jaafar, Wan Shafrina; Hermon, Dedi; Mokhtar, Ernieza Suhana (Jurnal Pendidikan Geografi Gea, 2021)
Coastal flood in Indonesia, namely as banjir rob, is a phenomenon that increases seawater to inundate around the tidal area. In Tanjungpinang, cases of coastal floods become a serious problem for people living in this area. This research aims to model the coastal flood inundation by modeling water inundation with a maximum level increase scenario. Its model was used to estimate coastal floods' impact on houses, buildings, and infrastructures with scenario 2 meters of sea-level rise.Â  On the other hand, the budget loss for restoration was estimated to study the effort of community adaptations with the ECLAC RAB method and observation to understand community adaptation. It was found that the spatial model succeeded in zoning inundation areas, which had a significant impact on houses, buildings, worship places, schools, and industrial at many 4112 units. From this case, the budget loss for the restoration of the physical environment was estimated at around 61994014.75 USD. In addition, the survey revealed the existing condition before and after the coastal flood. Several community efforts for adaptation were developing houses on stilt and hoarding the lowest land on-site location for build houses.